An Analysis of Solid Waste Disposal and Water Quality in Ugep Community, Cross River State, Nigeria - Eteng, Etim O.; Okputu, Joseph S.; Abetianbe, Christopher (Studia Ecologiae et Bioethicae, 2021)
The study carried out an analysis of solid waste disposal and its implication for water quality in the Ugep Community, located in Yakurr’s Local Government Council of Cross River State, Nigeria. Findings revealed that there is a significant and adverse relationship between solid waste disposal methods and the quality of drinking water, along with domestic uses in the study area. Data was collected through the administration of 500 questionnaires, with family heads as points of primary contact. It was clear that the poor state of infrastructural development and the challenge of availability and access to requisite amenities, coupled with inefficient management of the few available resources, has further exposed inhabitants to health and welfare issues. Results indicate a significant relationship between the solid waste disposal (sanitation) method and water quality in the study area. Awareness creation on sanitary practices by health and related government agencies, as well as community members themselves, should be encouraged to participate, as it will ensure a sustainable and health-oriented waste disposal system, bearing in mind likely concerns for water quality. Contamination of water is more prevalent in stored water, especially at the point of usage, as compared to where water flows freely, and is used without being stored. If water quantity is massive, the challenge of low quality is easily resolved, as less sanitation problems would occur. Government and private organisations should implement and encourage economic empowerment initiatives, in order to improve the livelihoods of the residents of the community.